Valuing Children's Voices - Mary Alice Barksdale; Cheri F Triplett (Arizona State University, 2010)
This paper explores the voices of elementary children in public schools. Three data bases were used including (a) interviews with 25 elementary students, (b) drawings and writings created by 225 third through sixth-grade students about their high stakes testing experiences, and (c) observations in two first-grade classrooms. The data demonstrate that elementary children have much to say about their overall school experiences, including their worries at school, their feelings of disconnect with their teachers, the lack of meaningful learning experiences, and their desire to be heard as unique individuals. These findings challenge educators to make changes in American classrooms in order to best meet the needs of young children.